Strategi Fundraising Dalam Meningkatkan Jumlah Muzakki Di LAZISMU Kota Metro - Hidayatullah, Farid; Hendri, Nedi; Febri Darmayanti, Elmira (Universitas Muhammadiyah Metro, 2024)
This study aims to find out how fundraising strategies in increasing muzakki in LAZISMU Metro City. This research uses qualitative research methods with a descriptive approach. Data collection techniques in this study are observation, interviews, and documentation. The results of this study are known that the strategy carried out by LAZISMU Metro City has three stages, namely the formulation, implementation, and evaluation stages. LAZISMU Metro City formulated three main strategies 1. Improve socialization and communication in the community, 2. Easy payment system, 3. Create a good brand image. After being formulated, it is then implemented in way 1. Conducting zakat campaigns or zakat socialization, 2. Opening a zakat booth, 3. Easy Payment System, 4. Implementing MSME, social, health, and da'wah empowerment programs. After the next stage of implementation, the evaluation stage of the evaluation results carried out by LAZISMU Metro City is quite good because it has implemented or implemented the strategies that have been set, although there are some that are not optimal